Building Communication Ethics in the Leadership of the Junior State 2 High School in Gorontalo, OSIS Management for the 2022-2023 Period - Muda, Lisdawati; Mala, Abdurrahman R. (International Journal of Scientific Research and Management (IJSRM), 2024)
This article investigates the significance of communication ethics in shaping the leadership dynamics among OSIS (Organization of Islamic Students) administrators within educational institutions. Through empirical analysis, it is revealed that adherence to communication ethics profoundly influences the effectiveness of OSIS administrators, facilitating smooth execution of diverse OSIS activities and fostering strong interpersonal bonds among administrators and members alike. Moreover, the integration of communication ethics fosters harmonious collaboration between OSIS supervisors, teachers, parents, and administrators, thereby cultivating a conducive environment for organizational growth and development. Furthermore, the application of communication ethics within the leadership framework of OSIS administration augments administrators' cognitive capacities, skill sets, and overall achievements, both academically and in extracurricular endeavors. This study underscores the pivotal role of communication ethics in enhancing leadership efficacy and fostering holistic development within the OSIS management milieu.